NSGAII Applied to Unified Second Level Cache Memory Hierarchy Tuning Aiming Energy and Performance Optimization - Cordeiro, F. R.; Silva-Filho, A. G. e (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2010: Anais do XI Simpósio em Sistemas Computacionais de Alto Desempenho, 2010)
The evolutionary algorithm NSGAII was applied to the problem of cache memory hierarchy optimization, considering unified second level. The proposed multi-objective approach considers two main objectives: energy consumption and performance related to the number of cycles necessary to run an application. Experiments done with 18 applications from two benchmarks (Power Stone and Mibench) permitted to conclude that found solutions, when NSGAII is applied, are close to optimal solutions. Results also were compared with an existing heuristic (TECH-CYCLES) and was observed that the quality of results obtained are superior in all analyzed cases, being in average 187 times lower in terms of the cost function (FC=Energy x Cycles) that represents the two components: energy and cycles of the application. Evaluating the impact in terms of number of simulations and obtained results, could be noticed that NSGAII needs only 1% of search space, becoming competitive for architecture exploration with unified second level.